Validation of Sugarcane Clones for Quality Jaggery Production in North Coastal Zone of Andhra Pradesh - Sreedevi, P.; Adilakshmi, D.; Rao, P. V. K. Jaganadha; Padmavathi, P.; Kiranmai, K. (International Journal of Bio-resource and Stress Management, 2024)
The study was conducted at Regional Agricultural Research station, Anakapalle, Andhra Pradesh, India during two consecutive years i.e. 2020–2021 to identify suitable sugarcane varieties for quality jaggery production. Six promising early varieties (2016 A 332, 2016 A 480, 2016 A 291, 2016 A 151, 2016 A 387, 2016 A 275) along with one check variety (87 A 298) were studied for cane yield, jaggery recovery. Jaggery making is age-old cottage industry prevailing in rural India. It is the traditional sweetener produced by evaporating sugarcane juice in conventional open boiling system. The quality of jaggery mainly depends on the quality of sugarcane seed used for jaggery making. Generally farmers are preparing jaggery using the cane variety recommended for that area for high sugar recovery. The major factors that govern the jaggery farmer’s preference are color, texture, shelf-life and high jaggery recovery which mainly depends on sugarcane variety. The quality parameter of the jaggery prepared from these varieties was evaluated for sucrose %, reducing sugars %, color and moisture content. The variety 2016 A 332 recorded highest cane yield (129 t ha-1) with jaggery recovery of 11% with highest sucrose % (86.7) and bright color. Among the varieties under study, 2016 A 332 followed by 2016 A 480 and 2016 A 387 are recommended for large scale production of quality jaggery in North coastal region of Andhra Pradesh.